Sistem Pakar Untuk Rekomendasi Pembelian Produk Jamu Menggunakan Forward Chaining (Studi Kasus Jamu Mbah Djitoen) - Hidayatulloh, Marchasyah Arzulla Akbar; Ringo, Johny H. Siringo (LPPM STIKOM Tunas Bangsa, 2024)
Jamu mbah djitoen is a shop that operates in the culinary sector selling homemade herbal medicine and juice. So far, the sales process has been conventional, customers come to the shop or send products using online motorcycle taxi services. Based on these problems, researchers will design a system that is developed based on a website and is equipped with a forward chaining expert system. The system design adapts the waterfall method, using MySQL as a database and using UML as a form of documentation for the system created. After designing the program and web hosting, black box testing was carried out on the system and involved 31 respondents to evaluate the system. The evaluation results obtained were 98% for a positive response to the system that had been created. It can be concluded that the expert system designed is able to help owners and customers.